Design of Planar Microstrip Ultrawideband Circularly Polarized Antenna Loaded by Annular-Ring Slot - Zhong-Hua Ma; Jia-Xiang Chen; Peng Chen; Yan Feng Jiang (International Journal of Antennas and Propagation)
A miniaturized planar microstrip circularly polarized ultrawideband (UWB) antenna loaded by annular-ring slot is proposed and implemented in the paper. With the annular-ring slot loaded in the radiating patch of the antenna, the side of the radiating patch is connected by the asymmetric inverted L-shaped microstrip. At the same time, a quarter of a circle is cut off from the radiating patch. The above designed structure shows improvements on the operating frequency band and realization of the circular polarization radiation. A tapered microstrip is placed between the feed line and the radiating patch to achieve the slow-changing impedance transformation. The results of simulation and measurement demonstrate that the 3 dB axial ratio (AR) fractional bandwidth of the antenna structure achieves 21.25%. The peak gain within the 3 dB axial ratio bandwidth fluctuates between 3.74 and 4.59 dBi. The antenna shows good impedance matching in the ultrawideband range. With the compact structure of the UWB antenna, it has potential application in various wireless communication devices.